Distopia Yohanes 12: Narasi Katarsis Rasul Yohanes dalam Periode Konflik - Valentino Wariki; Yusak Setianto; Muryati Muryati Muryati (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
This study begins by addressing compositional gaps in John 12 and its dynamic relationship with the Synoptic Gospels through an initial exegetical exploration. The findings are then developed into a narrative-historical analysis and interpreted using philosophical hermeneutics and catharsis theory to examine the internal condition of the Gospel’s author. The results indicate that John’s emotional state and underlying motives significantly influenced the structure and emphasis of chapter 12. His inner conflict as a disciple closely linked to both John the Baptist and Jesus underlies the unique features of this chapter when compared to the Synoptic parallels. Through cathartic contemplation, John is able to reimagine and narrate painful events with theological and pastoral depth. He recognises the necessity of recording these events faithfully so that his readers might perceive their profound meaning. Ultimately, the narrative conveys a striking message: the world is no longer a safe or ideal place for the followers of Christ. Rather, it has become a dystopian reality, underscoring the cost of discipleship and the enduring relevance of John's Gospel for a suffering community.